2010
DOI: 10.1375/ajgc.20.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Examining School Related Factors Leading to Dropout Through Children's Conceptions and Experiences: Development of a Scale for Attitudes Towards Elementary School

Abstract: Despite state support for mass education in Turkey, there are many primary school children who do not attend school or who drop out before finishing school. This study is part of a project investigating the problem of school dropout in a district of Istanbul. Factors related to school, such as failure, non-acceptance by teachers and peers, poor attendance, and low levels of involvement, have been associated with increased likelihood of dropout. Modifying the instructional environment, strengthening school memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Studies indicate that students (particularly boys) who perceive relationships with teachers as negative are at a significantly greater risk of dropping out (Lessard et al, 2004). Additionally, positive relationships with peers, the feeling of belonging, absence of peer violence, as well as participation in extracurricular activities and different kinds of dialogue in the classroom and school are related to lower incidence of dropping out of educational system (Christle, Jolivette & Nelson, 2007;Erktin, Okcabol & Ural, 2010;European Commission, 2015;Fortin et al, 2013;Pooley et al, 2008). Furthermore, it has been shown that strict measures for punishing students with disciplinary problems or poor attendance represent a significant factor connected to dropping out.…”
Section: Dropping Out Of Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicate that students (particularly boys) who perceive relationships with teachers as negative are at a significantly greater risk of dropping out (Lessard et al, 2004). Additionally, positive relationships with peers, the feeling of belonging, absence of peer violence, as well as participation in extracurricular activities and different kinds of dialogue in the classroom and school are related to lower incidence of dropping out of educational system (Christle, Jolivette & Nelson, 2007;Erktin, Okcabol & Ural, 2010;European Commission, 2015;Fortin et al, 2013;Pooley et al, 2008). Furthermore, it has been shown that strict measures for punishing students with disciplinary problems or poor attendance represent a significant factor connected to dropping out.…”
Section: Dropping Out Of Schoolmentioning
confidence: 99%
“…Having examined relevant reference works (Christle, Jolivette & Nelson, 2007;Erktin, Okcabol & Ural, 2010;Fortin et al, 2013;Lessard et al, 2004;Lyche, 2010;Pooley et al, 2008), we identified the areas of school life and work which can be associated with dropping out of educational system. Therefore, interview and focus group guidelines covered the following topics: (1) Physical conditions in school, (2) Teacher-student relationship and emotional 56 PSIHOLOŠKA ISTRAŽIVANJA VOL.…”
Section: Data Gathering and Analysis Techniquesmentioning
confidence: 99%
“…Since students spend a considerable amount of time at school, belonging is considered to be a precursor of a stable school experience (Erktin, Okcabol & Ural, 2010). Although the sense of belonging is linked to, inter alia, respect for teachers, participation, academic success, and liking school (Furman, 2002), this research suggests that experience of ostracism and the feelings of isolation meant that the re-enrolled dropouts did not feel a sense of belonging in the school community.…”
Section: Social Categorisation and Dropout Reintegrationmentioning
confidence: 79%
“…Although the sense of belonging is linked to, inter alia, respect for teachers, participation, academic success, and liking school (Furman, 2002), this research suggests that experience of ostracism and the feelings of isolation meant that the re-enrolled dropouts did not feel a sense of belonging in the school community. Students who feel isolated are more likely to fail (Beck & Malley, 1998), which is disturbing because previous research has shown that academic failure is a major cause of drop out (Brown, 2010;2012;Chuang, 1997;Erktin et al, 2010). Unless the situation of social segmentation is reversed, and a strong sense of community is actively cultivated and supported, there is a risk that the re-enrolled dropouts could be pushed out and become victims of repeat drop out.…”
Section: Social Categorisation and Dropout Reintegrationmentioning
confidence: 99%
“…Benzer şekilde Tunç'un (2011) çalışmasında başarısızlık, okul terkinde birinci neden olarak bulunmuş; bunu disiplin sorunu yaşama ve bir an önce para kazanma ihtiyacı nedenleri izlemiştir. Özdemir, Sezgin, Şirin, Karip ve Erkan (2010a) Alanyazın incelendiğinden okul terk nedenlerinin okul, çevre, aile ve birey başlıkları altında gruplandırıldığı, ailedeki sosyal ve ekonomik durumun (Gökşen, Cemalcılar ve Gürlesen, 2006), akran ve öğretmen desteği hissetmenin ve (Taş, Selvitopu, Bora ve Demirkaya, 2013;Özdemir, Sezgin, Şirin, Karip ve Erkan, 2010b) öğrencinin akademik başarısının (Erktin, Okçabol ve Ural, 2010) önemine değinilmiştir. Yorğun (2014), düşük sosyal destek hissetmenin, olumsuz akran ilişkilerinin, okula ve eğitime karşı olumsuz tutumların, bireyin özsaygısının düşük olmasının ve kendini ortamdan geri çekmesinin bileşeni olarak okul terk riskinin arttığını ifade etmiştir.…”
unclassified